New classification of liver biopsy assessment for fibrosis in chronic hepatitis B patients before and after treatment - Sun, Yameng; Zhou, Jialing; Wang, Lin; Wu, Xiaoning; Chen, Yongpeng; Piao, Hongxin; Lu, Lungen; Jiang, Wei; Xu, Youqing; Feng, Bo; Nan, Yuemin; Xie, Wen; et al. (Hepatology (Baltimore, Md.), 2017)
Liver fibrosis is the net result of dynamic changes between fibrogenesis and fibrolysis. Evidence has shown that antiviral therapy can reverse liver fibrosis or even early cirrhosis caused by hepatitis B virus. However, current evaluation systems mainly focus on the severity of, but not the dynamic changes in, fibrosis. Here, we propose a new classification to evaluate the dynamic changes in the quality of fibrosis, namely: predominantly progressive (thick/broad/loose/pale septa with inflammation); predominately regressive (delicate/thin/dense/splitting septa); and indeterminate, which displayed an overall balance between progressive and regressive scarring. Then, we used this classification to evaluate 71 paired liver biopsies of chronic hepatitis B patients before and after entecavir‐based therapy for 78 weeks. Progressive, indeterminate, and regressive were observed in 58%, 29%, and 13% of patients before treatment versus in 11%, 11%, and 78% after treatment. Of the 55 patients who showed predominantly regressive changes on posttreatment liver biopsy, 29 cases (53%) had fibrosis improvement of at least one Ishak stage, and, more interestingly, 25 cases (45%) had significant improvement in terms of Laennec substage, collagen percentage area, and liver stiffness despite remaining in the same Ishak stage. Conclusion: This new classification highlights the importance of assessing and identifying the dynamic changes in the quality of fibrosis, especially relevant in the era of antiviral therapy.(Hepatology 2017;65:1438‐1450)